Prospective Cohort Study on the Impact of Early Versus Late Inpatient Palliative Care on Length of Stay and Cost of Care. (July 2023) - Srinivasan, Vamshek J.; Akhtar, Saad; Huppertz, John W.; Sidhu, Mandeep; Coates, Andrew; Knudsen, Nancy
Aim: To evaluate the impact of early vs late palliative care on (1) length of stay (LOS) in the context of expected LOS measures and (2) total cost of care to the hospital for each patient.Methods: A prospective cohort study was performed at a single large academic medical center on patients who received an inpatient palliative care consultation. The two cohorts were early palliative care (within 3 days of admission) and late palliative care (after 3 days of admission). Comparisons were made between patients' actual LOS, expected LOS, and total hospital costs between both cohorts.Results: Compared to the late palliative care cohort (N = 126), patients who received early palliative care (N = 68) had a significantly shorter LOS ( P < .001) and also performed better compared to CMS-Expected LOS standards (Observed/Expected 3.1 vs 1.5 respectively; P < .001). Early palliative care patients also saw an average decline of 1431 in total costs 1-day pre/post consult as opposed to a more modest 403 decline in the later palliative care cohort ( P < .001). Similarly, patients who received early palliative care had a 5839 decline in aggregated total 3-day costs, as opposed to a 1478 decline in those who received late palliative care ( P < .001).Conclusions: In the competitive and rapidly evolving healthcare system, the opportunity to suppress costs and lower patient LOS has increasing importance. Our study strongly supports the implementation of earlier palliative care intervention to assist hospitals in approaching LOS targets and reducing patient costs.